Knowledge Liaisons: Negotiating Multiple Pedagogies in Global Indigenous Studies Courses - Augustus, Camie (Canadian Journal of Higher Education, 2015)
Over the past few years, Canadian universities have been at the forefront of institutional changes that identify Aboriginal people, internationalization, and pedagogical change as key areas for revision. Most universities’ strategic planning documents cite, at least to varying degrees, these three goals. Institutions have facilitated these changes by supporting new programs, teaching centres, and course redevelopment. While much attention has been given to those goals individually, it is rarely considered how these commitments converge in particular course offerings. This article considers the connections among Indigenous, global, and pedagogical goals by examining undergraduate comparative Indigenous studies courses, some pedagogical challenges that arise in those courses, and some strategies I have developed in meeting those challenges. Based in auto-pedagogy and a critical analysis of existing and emerging pedagogical frameworks, this article uses key concepts from Indigenous epistemologies, knowledge translation, and Sue Crowley’s (1997) levels of analysis to propose “knowledge liaisons” as a teaching model that addresses these challenges.